From Policy to Practice: Shaping the Future of Vocational Education in China through Enhanced Management Strategies - Zhu Yao; Astri Yulia; Latifah Abd Latib (Research Synergy Foundation, 2026)
China's vocational education system faces significant challenges in translating policy directives into effective educational practice amid rapid socio-economic transformation. This study examines management strategies employed by Chinese vocational colleges, investigates the effectiveness of policy implementation, and identifies contextual factors that influence outcomes. Using systematic document analysis of academic publications and policy documents, the research maps institutional management approaches across curriculum governance, faculty development, and digital integration, and evaluates their impact on graduate employability and stakeholder satisfaction. Three primary themes emerged from the analysis: career planning systems, entrepreneurship education initiatives, and structured internship programs. Policy document analysis reveals national emphasis on integrating career guidance into curricula, promoting innovation-focused entrepreneurship education, and establishing quality-assured industry partnerships. However, significant implementation gaps persist between policy aspirations and institutional realities, particularly regarding regional disparities, resource limitations, and faculty preparedness. The findings indicate that while policy frameworks provide clear directional guidance, institutional capacity varies substantially across regions and sectors. Coastal institutions demonstrate more effective policy implementation due to stronger industry partnerships and resource availability, while inland institutions face structural disadvantages. The study recommends enhanced policy support for capacity building, strengthened industry collaboration mechanisms, and development of context-sensitive implementation strategies to bridge the persistent gap between vocational education policy and practice.